ENVIRONMENTAL IMPACT ON DIGITAL ERA BY ARCHITECTURAL PRODUCTION - Sandi, Reza (UI Scholars Hub, 2019)
Current developments in architecture and construction demand innovation in design. Increasing demand and rapid production time require mass production. Digital fabrication with the combination of computed design and robotic manufacturing is a development in architectural design. Digital fabrication is also a product of modernization, which affects various components of the environment as well as social, economic, and cultural components. This study aims to provide an overview of the technology upgrade in the architectural and construction sectors that affect the environment, starting from the process of architectural design and construction products in the digital era up to the impact of these activities on the environment. The method used is descriptive research—by conductingobservations from scientific evidence (literature studies) that support this research. First, the concept is described followed by the discussion of the production process of architectural design products in the current digital era and the influence of these activities on the environment, such as degradation on the aspects of the environment, economy, society, and culture. The results show that architectural production in the digital era has a negative impact on the environment due to architectural products created using digital fabrication systems as well as exploitation of natural resources, encouraging finance, and transportation of these products across borders. Social and cultural changes are degraded by local culture caused by cross-cultural, as well as a new phenomenon of universalization of culture (world culture) or what is now called the digital culture